Assessment of DSM–5 Section II Personality Disorders With the MMPI–2–RF in a Nonclinical Sample. Issue 4 (4th July 2017) - Sellbom, Martin; Smith, Alexander
ABSTRACT: The Minnesota Multiphasic Personality Inventory–2–Restructured Form (MMPI–2–RF; Ben-Porath & Tellegen, 2008 /2011 ) is frequently used in clinical practice. However, there has been a dearth of literature on how well this instrument can assess symptoms associated with personality disorders (PDs). This investigation examined a range of hypothesized MMPI–2–RF scales in predicting PD symptoms. We evaluated these associations in a sample of 397 university students who had been administered the MMPI–2–RF and the Structured Clinical Interview for DSM–IV Axis II Disorders–Personality Questionnaire (First, Gibbon, Spitzer, Williams, & Benjamin, 1997 ). Zero-order correlation analyses and negative binomial regression models indicated that a wide range of MMPI–2–RF scale hypotheses were supported; however, the least support was available for predicting schizoid and obsessive–compulsive PDs. Implications for MMPI–2–RF interpretation and PD diagnosis are discussed.